Highly efficient functionalized MOF-LIC-1 for extraction of U(vi) and Th(iv) from aqueous solution: experimental and theoretical studies. Issue 9 (10th February 2022) - Venkata Sravani, V.; Sengupta, Somnath; Sreenivasulu, B.; Gopakumar, Gopinadhanpillai; Tripathi, Sarita; Chandra, Manish; Brahmmananda Rao, C. V. S.; Suresh, A.; Nagarajan, Sivaraman
Abstract : Four MOF-LIC-1 MOFs following the PSM strategy were prepared, characterized, and examined for the sorption of U(vi ) and Th(iv ). Also the nature of U(vi ) interactions on MOFs was also investigated by applying DFT calculations. Abstract : A set of four new functionalized MOFs, namely MOF-LIC-DPPC, MOF-LIC-GA, MOF-LIC-PCA and MOF-LIC-SA, were synthesized via the post-synthetic modification (PSM) strategy using MOF-LIC-1 for efficient extraction of U(vi ) and Th(iv ) from an aqueous medium. FTIR, powder XRD, TGA and SEM-EDX were employed for characterization of the functionalized MOFs. Sorption studies for U(vi ) and Th(iv ) were performed by monitoring the pH and contact time. Interestingly, the modified MOF-LIC-SA displayed rapid (∼5 min) and efficient extraction towards U(vi ) and Th(iv ) from an aqueous medium and modified MOF-LIC-DPPC displayed enhanced thermal stability (600 °C) compared with the parent MOF-LIC-1 (450 °C). These studies revealed that the grafted functionalities on MOF-LIC-1 possess enhanced sorption efficiency towards U(vi ) and Th(iv ) as well as thermal stability. MOF-LIC-SA exhibited the highest sorption capacity towards U(vi ) and Th(iv ), viz . 298 mg g −1 (pH 6) and 149 mg g −1 (pH 6), respectively. Leaching, recyclability, and radiation stability studies were also performed using MOF-LIC-1 MOFs. Additionally, we investigated the nature of U(vi ) interactions on MOFs by applying density functional theory (DFT). PSM MOFs with various functionalities display high selectivity and efficient extraction of U(vi ) and Th(iv ) over a wide pH range (2–9) and also exhibit easy recovery of metal ions from MOFs. These studies reveal that U(vi ) and Th(iv ) can be extracted from aqueous streams in a pH range from 6 to 8 and potential applications of these MOFs include recovery of U(vi ) and Th(iv ) from mine water, sea water, etc . The studies reported in the present work also have extensive potential applications for environmental concerns as well as in the nuclear industry.